2014
DOI: 10.1007/s10751-013-0944-0
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies of Soltmany and Shisr 176 meteorites – comparison with other ordinary chondrites

Abstract: Two ordinary chondrites type L6: Soltmany and Shisr 176, were recently investigated in our laboratory. The distribution of iron in the 4 main iron bearing mineral phases (olivine, pyroxene, kamacite and troilite) determined by Mössbauer spectroscopy in Soltmany and Shisr 176 meteorites was very different from that in the Baszkowka meteorite (type L5). To explain the cause of this difference, a comparison of the distribution of iron among the main mineral phases present in other type L and H meteorites was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…; Galazka‐Friedman et al. ) analyzed whole rock samples and thus could not assign Fe 3+ , when detected, to any particular phase. Some workers (Shrivastava et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Galazka‐Friedman et al. ) analyzed whole rock samples and thus could not assign Fe 3+ , when detected, to any particular phase. Some workers (Shrivastava et al.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this is a difficult comparison to make because pyroxenes rarely make up 100% of any meteorite, and thus results must be indirectly interpreted from whole rock spectra or from time-consuming mineral separates. There have been numerous studies of meteorites by M€ ossbauer spectroscopy but the results are mixed because most of them (e.g., Malasheva 1994;Abdu and Ericsson 1997;Lipka et al 1997Lipka et al , 2013Lipka et al , 2014Grandjean et al 1998;Rusakov et al 2000;Ludwig et al 2001;Hoffman 2002;Verma et al 2003;Gismelseed et al 2004Gismelseed et al , 2005Zhiganova et al 2007;Oshtrakh et al 2008aOshtrakh et al , 2008bGrokhovsky et al 2009;Sitek et al 2012;Galazka-Friedman et al 2014) analyzed whole rock samples and thus could not assign Fe 3+ , when detected, to any particular phase. Some workers (Shrivastava et al 1997;Munayco et al 2013;Gismelseed et al 2014;Maksimova et al 2015) studied fresh falls and found little or no Fe 3+ , but in most cases the whole rock spectra are so complicated that Fe 3+ was unlikely to be detected.…”
Section: Comparisons With Meteoritic Pyroxenesmentioning
confidence: 99%
“…Our group has published three papers on this subject (Gałązka‐Friedman et al. , ; Szlachta et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years several studies on the use of Mössbauer spectroscopy for classification of ordinary chondrites were published [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%